Studi Pendahuluan Mikroba Endofitik Penghasil Senyawa Terpen dari Tanaman Artenisia annua - Titi Parwati; Bustanussalam Bustanussalam; Partomuan Simanjuntak (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
Some endophytic microbes were isolated from medicinal plant Artemisia annua collected of Tawangmangu and Cibinong. Microbe isolate were made on corn meal malt agur supplemented with chloramphenicol and nutrient agar supplemented with nystatin from tissue subjected after the triple surface sterilization procedure. The potencies of these isolates to produce-terpene compounds were screenned by phytochemistry analysis, thin layer chromatography (tlc) and high performance liquid chromatography (hplc) after fermentation in four different medium. The results showed that 6 isolates from 17 microbe isolates can produce terpene compounds.